2015
DOI: 10.1152/ajpheart.00497.2014
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein phosphorylation in excitation-contraction coupling in taurine deficient hearts

Abstract: Ramila KC, Jong CJ, Pastukh V, Ito T, Azuma J, Schaffer SW. Role of protein phosphorylation in excitation-contraction coupling in taurine deficient hearts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 53 publications
1
44
0
Order By: Relevance
“…Moreover, the similarity between the actions of rotenone and those of β-alanine [21] implies that β-alanine-mediated reductions in complex I activity also cause a diversion of electrons from complex I to the acceptor oxygen, forming in the process superoxide. Thus, β-alanine treatment is associated with diminished ATP generation and energy metabolism, as well as elevated oxidative stress, factors that are capable of altering the contractile state of the failing heart [28, 29]. These results support the suggestion that β-alanine-mediated oxidative stress contributes to the development of tissue dysfunction, including diminished muscle function and hypotonia.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, the similarity between the actions of rotenone and those of β-alanine [21] implies that β-alanine-mediated reductions in complex I activity also cause a diversion of electrons from complex I to the acceptor oxygen, forming in the process superoxide. Thus, β-alanine treatment is associated with diminished ATP generation and energy metabolism, as well as elevated oxidative stress, factors that are capable of altering the contractile state of the failing heart [28, 29]. These results support the suggestion that β-alanine-mediated oxidative stress contributes to the development of tissue dysfunction, including diminished muscle function and hypotonia.…”
Section: Discussionsupporting
confidence: 57%
“…Figure 5d shows that β-alanine-mediated apoptosis is completely prevented by cyclosporin A, suggesting that activation of the MPT pore is an important contributor to β-alanine-mediated apoptosis. It is interesting that β-alanine exposure reduces the relaxation phase of the Ca 2+ transient, largely by decreasing sarcoplasmic reticular Ca 2+ ATPase activity secondary to diminished phospholamban phosphorylation [28]. These changes in [Ca 2+ ] i may act synergistically with oxidative stress to initiate the mitochondrial permeability transition.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac taurine depletion directly alters the calcium sensitivity of myofibrillar proteins, through impaired sarcoplasmic reticulum calcium ATPase activity and reduced phospholamban phosphorylation. Collectively, these defects yield abnormalities in both systolic and diastolic function (Ramila et al, ). Taurine also acts to attenuate the detrimental effects of catecholamines and angiotensin II in heart failure (Ito et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Not only do damaged mitochondria elevate the risk of cardiomyocyte death, but they also diminish ATP generation and increase ROS production. Recently, Ramila et al (2015) reported that the taurine-deficient cardiomyopathy is also associated with sarcoplasmic reticular Ca 2+ mishandling. The present study raises the possibility that an imbalance in the turnover of proteins, coupled with the accumulation of damaged proteins, may further weaken the TauTKO heart.…”
Section: Discussionmentioning
confidence: 99%
“…Several physiological actions have been attributed to taurine, with metabolic, antioxidant, anti-inflammatory and cytoprotective activities being the most important (Mozaffari et al 1986;Jong et al 2012;Marcinkiewicz and Kontny 2014;Ramila et al 2015). Maintenance of high tissue taurine levels is required for normal cellular function, as taurine deficiency is associated with the development of cardiomyopathy, neuropathy, retinopathy, developmental defects and pregnancy complications (Knopf et al 1978;Sturman et al 1985;Sturman and Messing 1992;Schuller-Levis et al 1990;Ito et al 2008).…”
Section: Introductionmentioning
confidence: 99%